2020
DOI: 10.1155/2020/6341093
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Prognostic Value of Gastric Carcinoma Highly Expressed Transcript 1 in Cancer: A Meta-Analysis

Abstract: Background. Long noncoding RNA gastric cancer highly expressed transcript 1 (lncRNA GHET1) is often reported to be abnormally expressed in multiple cancers, but the situation is different in different cancers. Therefore, a meta-analysis is necessary to clarify the value of lncRNA GHET1 as a prognostic indicator in cancer. Methods. Relevant research studies on lncRNA GHET1 and cancer were retrieved from three electronic literature databases of Web of Science, PubMed, and OVID. Meanwhile, hazard ratios (HRs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Previous studies have confirmed that lncRNAs are involved in tumorigenesis, as well as in the treatment and prognosis of tumors (17,(31)(32)(33). For example, Xu et al found that up-regulation of lncRNA-CCHE1 could promote gastric cancer cell proliferative ability and colony formation, inhibiting cell apoptosis; however, low-expression of lncRNA-CCHE1 had the opposite effect.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have confirmed that lncRNAs are involved in tumorigenesis, as well as in the treatment and prognosis of tumors (17,(31)(32)(33). For example, Xu et al found that up-regulation of lncRNA-CCHE1 could promote gastric cancer cell proliferative ability and colony formation, inhibiting cell apoptosis; however, low-expression of lncRNA-CCHE1 had the opposite effect.…”
Section: Discussionmentioning
confidence: 93%
“…APC Min/+ mice are an ideal mouse model for studying the mechanism of CRC [37]. Previously, studies have found that lncRNA can participate in the occurrence and development of tumors through various molecular mechanisms and can serve as targets for cancer diagnosis, treatment, and prognosis prediction [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, the diversified results, the heterogeneity of lncRNAs biology and prognosis, as well as the presence of different treatment options make the clinical decision-making process highly varied. Thus, a series of systematic reviews and meta-analyses have been conducted to provide further evidences on the relationship between variants of dysregulated lncRNAs and prognosis of cancer ( Chen C et al, 2018 ; Quan et al, 2018 ; Tian et al, 2018 ; Zhang S et al, 2020 ; Yang et al, 2020 ; Zhou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%